Responding to public and private politics: corporate disclosure of climate change strategies - Reid, Erin M.; Toffel, Michael W. (Strategic Management Journal, 2009)
Abstract The challenges associated with climate change will require governments, citizens, and firms to work collaboratively to reduce greenhouse gas emissions, a task that requires information on companies' carbon risks, opportunities, strategies, and emission levels. This paper explores the conditions under which firms participate in this endeavor. Building on theories of how social activists inspire changes in organizational norms, beliefs, and practices, we hypothesize that shareholder actions and regulatory threats are likely to prime firms to adopt practices consistent with the aims of a broader social movement. We find empirical evidence of direct and spillover effects. In the domain of private politics, shareholder resolutions filed against a firm and others in its industry increase a firm's propensity to engage in practices consistent with the aims of the related social movement. Similarly, in the realm of public politics, threats of state regulations targeted at a firm's industry as well as regulations targeted at other industries increase the likelihood that the firm will engage in such practices. These findings extend existing theory by showing that both activist groups and government actors can spur changes in organizational practices, and that challenges mounted against a single firm or a single industry can inspire both firm and field‐level changes. Copyright © 2009 John Wiley & Sons, Ltd.